Effectiveness of nurse-targeted education interventions on clinical outcomes for patients with indwelling urinary catheters: A systematic review. (May 2022) - Alex, Joby; Maneze, Della; Ramjan, Lucie M.; Ferguson, Caleb; Montayre, Jed; Salamonson, Yenna
Abstract: Objectives: To identify subject matter, pedagogical approaches and assess outcomes of interventions implemented to educate nurses in urinary catheterisation care and management. Design: A systematic review was conducted according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement. Data sources: Databases (CINAHL; MEDLINE; ProQuest; ERIC; Scopus; Cochrane; and APA PsycINFO) were searched using key concepts: education interventions, indwelling urinary catheter and nurses, from inception to July 2021. Review methods: Two researchers searched the databases, whereupon data were extracted using a standardised proforma and were analysed applying an abductive approach. The Joanna Briggs Institute Critical Appraisal tool was used to assess the quality of the included studies. Findings were analysed and reported using narrative synthesis. Results: Out of 1159 studies screened, nine educational intervention studies related to upskilling nurses in catheter management were identified. Subject matter addressed included pathophysiology of the urinary system, clinical indications and management of indwelling catheter and associated complications. Although the subject matter and pedagogical approaches varied, all identified studies reported positive effects in improving participants' knowledge. Conclusions: Upskilling nurses and increasing their confidence to deliver patient-centred catheter care practices is an important intervention to improve outcomes for patients with long-term indwelling urinary catheters. However, actively engaging nurses who provide direct patient care is essential, in planning and implementing targeted educational interventions specific to learning needs. This review has identified a gap in the educational interventions for nurses, in better supporting the psychosocial needs of patients living with indwelling catheter. Codesigning educational interventions with nurses that are tailored to their contextual learning needs is likely to enhance behaviour change and improve current practice.